(untitled) (MASKAY, 2021)
This article reviews the Citizen Broadband Radio Service (CBRS) and its characteristics. It also describes the Spectrum Access System, which allows the bands not used by primary users to be intelligently occupied by secondary users to optimize this resource. As a rule, CBRS operates between 3550 and 3700 MHz, allowing users to connect with operators in high-traffic locations. Using Neutral Hosts minimizes the installation and operation costs of the Advanced Mobile Service’s operators. CBRS also functions as a private LTE network with several advantages over other wireless network technologies. This innovative proposal marks a milestone in shifting from fixed radio spectrum allocation to dynamic controlled access, enabling connectivity to a wide range of wireless devices.